Low Self-Control and Environmental Harm: A Theoretical Perspective and Empirical Test - Partin, Raymond (American journal of criminal justice, 2020)
Research finds low self-control is associated with a myriad of delinquent, criminal, and antisocial behaviors. Less attention, however, has been directed at investigating whether low self-control is related to environmental harm. The current study contributes to this area of research in two ways. First, we explicate why low self-control would relate to environmental harms committed by individuals. Second, using data collected on a sample of approximately 500 adults from southeastern Florida, we test whether low self-control is associated with the specific environmental harm of littering. Results indicate low self-control increases the likelihood of both past littering behavior as well as projected littering behavior. Supplementary analyses demonstrate low self-control is associated with higher frequency littering but not lower frequency littering. Discussion centers on the implications of the findings, study limitations, and a call for additional research to investigate the association between low self-control and a broader array of environmental harms.